2020
DOI: 10.3390/app10155112
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Design and Design Parameter Sensitivity Analyses of an eVTOL PAV in the Conceptual Design Phase

Abstract: An optimization study of an electric vertical takeoff and landing personal air vehicle (eVTOL PAV) was performed during the conceptual design stage using the design of experiments method. In defining the initial problem, a design target parameter was set. The PAV subsystem was based on a configuration tradeoff study matrix, which was used to effectively conduct configuration selection. Initial sizing was performed using the PAV sizing program developed by this research team using Microsoft Excel and Visual Bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 6 publications
(12 reference statements)
0
2
0
Order By: Relevance
“…Most eVTOL designs converge to a comparable size because aircraft weight increases with the cube of aircraft capacity before running into the limitations of available battery and charging station technologies (Warren, Garbo, Herniczek, Hamilton, & German, 2019). Lee et al (2020) found that the MTOW has a direct effect on aircraft performance in terms of range, cruise speed, and stall speed (Lee, Tullu, & Hwang, 2020). Akash et al (2022) presented the design of a TR eVTOL aircraft that they expect to carry 500-kilograms of payload for 500 kilometers by assuming the use of a 600 Wh/kg lithium-sulphur battery (Akash, et al, 2022).…”
Section: Flight Range Projectionsmentioning
confidence: 99%
“…Most eVTOL designs converge to a comparable size because aircraft weight increases with the cube of aircraft capacity before running into the limitations of available battery and charging station technologies (Warren, Garbo, Herniczek, Hamilton, & German, 2019). Lee et al (2020) found that the MTOW has a direct effect on aircraft performance in terms of range, cruise speed, and stall speed (Lee, Tullu, & Hwang, 2020). Akash et al (2022) presented the design of a TR eVTOL aircraft that they expect to carry 500-kilograms of payload for 500 kilometers by assuming the use of a 600 Wh/kg lithium-sulphur battery (Akash, et al, 2022).…”
Section: Flight Range Projectionsmentioning
confidence: 99%
“…The whole process is pictorially represented in the flowchart in Figure 4 [29]. The comprehensiveness and accuracy of the results have made this statistical optimization technique an integral component for precise result-oriented problems.…”
Section: Design Of Experimentsmentioning
confidence: 99%
“…Sensitivity analysis of the design parameters can clarify the impact of each parameter on the specific performance indicators, and then provide a reference for the selection of the design parameters and the optimization of the design scheme. Lee et al [23] conducted a sensitivity analysis of the design parameters of the eVTOL aircraft, but it seems that the tilting transition segment was not considered in the mission performance analysis.…”
Section: Introductionmentioning
confidence: 99%